2019
DOI: 10.1002/cbdv.201800575
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Year Bio‐Agronomic and Chemotaxonomic Evaluation of Wild Sicilian Myrtle (Myrtus communis L.) Berries and Leaves

Abstract: A collection of nine Myrtus communis samples from different localities of Sicily was evaluated. Morphological traits and production characteristics have been chosen as parameters to arrange the samples into homogeneous groups and to identify the best biotypes for possible future agro‐industrial exploitation. The plant material has been subjected to taxonomic characterization from biometric and phytochemical perspectives. Myrtle berries and leaves have been analyzed for their content in metabolites, applying a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…The fragmentation pattern of anthocyanins is consistent with previously reported data [38,47]. Maldini et al (2016) [47], Sarais et al (2016) [66], Scorrano et al (2017) [67] and Siracusa et al (2019) [68] reported that anthocyanins in myrtle berries are mainly represented by delphinidine-3-O-glucoside, petunidin-3-O-glucoside, malvidine-3-O-glucoside, and peonidine-3-glucoside, followed by cyanidine-3-glucoside, delphinidinpentoside and petunidin-pentoside. Content of total ANT in analyzed extracts of myrtle berries was in range from 297.38 to 947.13 mg/100 g dm.…”
Section: Characterization Of Selected Map Extracts By Uplc-esi/ms2 Analysissupporting
confidence: 91%
“…The fragmentation pattern of anthocyanins is consistent with previously reported data [38,47]. Maldini et al (2016) [47], Sarais et al (2016) [66], Scorrano et al (2017) [67] and Siracusa et al (2019) [68] reported that anthocyanins in myrtle berries are mainly represented by delphinidine-3-O-glucoside, petunidin-3-O-glucoside, malvidine-3-O-glucoside, and peonidine-3-glucoside, followed by cyanidine-3-glucoside, delphinidinpentoside and petunidin-pentoside. Content of total ANT in analyzed extracts of myrtle berries was in range from 297.38 to 947.13 mg/100 g dm.…”
Section: Characterization Of Selected Map Extracts By Uplc-esi/ms2 Analysissupporting
confidence: 91%
“…Concerning leaves composition, the concentration of total polyphenols and flavonoids varies from 31.25 to 298.63 mg GAE/g and from 129.96 to 376.82 mg/g, respectively, according to the myrtle variety and the methods applied for extraction and analysis (Amensour et al., 2010; Özcan et al., 2020). In particular, lignans (i.e., secoisolariciresinol hexoside), tannins (i.e., eugeniflorin D2, tellimagrandin I and II, and oenothein B), flavonoids (i.e., (+)‐catechin, quercetin 3‐O‐rhamnoside, quercetin‐galactoside‐gallate, (–)‐epigallocatechin, (–)‐epigallocatechin 3‐ O ‐gallate, myricetin galactoside, myricetin 3‐O‐rhamnoside, myricetin arabinoside, and kaempferol‐ O ‐galloyl‐hexoside), phenolic acids (i.e., ellagic acid and derivatives, gallic acid and galloyl derivatives, syringic acid, t‐ferulic acid, and caffeic acid), and gallomyrtucommulones (i.e., gallomyrtucommulone A and C) are the main phytochemicals found in myrtle leaf extracts (Babou et al., 2016; Özcan et al., 2020) (Figure 4; Pereira et al., 2016, 2017; Siracusa et al., 2019; Taamalli et al., 2014; Viuda‐Martos et al., 2011; Yoshimura, Amakura, Tokuhara, & Yoshida, 2008).…”
Section: Proximal Nutritional and Phytochemical Composition Of Myrtlementioning
confidence: 99%
“…Most common monoterpenes and sesquiterpenoids found in myrtle-derived essential oils petunidin 3-O-glucoside, malvidin 3-O-glucoside, and peonidin 3-Oglucoside, followed by cyanidin 3-O-glucoside, delphinidin-pentose, and petunidin-pentose (Maldini et al, 2016;Montoro et al, 2006;Pereira, Cebola, Oliveira, & Gil, 2016, 2017Sarais et al, 2016;Scorrano et al, 2017;Siracusa et al, 2019) (Figure 3; Snoussi et al, 2012;Tuberoso et al, 2010).…”
Section: Phytochemical Content Of Myrtlementioning
confidence: 99%
See 2 more Smart Citations